The Potential Topics as Discourse Shapers Argumentation The Forum Holds a Talk With the Theme of the Covid-19 Pandemic: Pragma-dialectical Studies - Kamariah Kamariah; Kisyani Laksono; Agusniar Dian Savitri (International Journal Of Education, Social Studies, And Management (IJESSM), 2023)
The purpose of writing this article is to find potential topics with dialectical objectives and potential topics with rhetorical objectives as argumentation makers at each stage of critical discussion at the COVID-19-themed talk forum. The method used is descriptive qualitative with data analysis techniques emphasizing pragma-dialectical studies focusing on argumentative discourse. Data analysis techniques emphasize pragma-dialectical studies focusing on argumentative discourse. The results showed that potential topics with dialectical and rhetorical functions were found at each stage of the argumentation. Each function found has a different role as an argumentative. Potential topics with an analytic function in the confrontation stage are used to explain the issues discussed. The opening stage ensures that disputes exist and are unambiguous. At the argumentation stage, it is used to test the acceptance of a descriptive, evaluative, or prescriptive point of view. The closing stage ensures that everything that has been said is concluded with sufficient evidence. At the same time, the potential topics with a rhetorical function in the confrontation stage are used to ensure that the issues in the discussion degree are helpful. In the opening stage, it is used to select arguments that do not involve the burden of proof. At the argumentation stage, it is used to apply persuasion tools that will make someone win the argument. The closing stage is used to ensure the argument ends.